Mdm2 Promotes Genetic Instability and Transformation Independent of p53 - Bouska, Alyssa (American Society for Microbiology (ASM), 2008)
Mdm2, a regulator of the tumor suppressor p53, is frequently overexpressed in human malignancies. Mdm2 also has unresolved, p53-independent functions that contribute to tumorigenesis. Here, we show that increased Mdm2 expression induced chromosome/chromatid breaks and delayed DNA double-strand break repair in cells lacking p53 but not in cells with a mutant form of Nbs1, a component of the Mre11/Rad50/Nbs1 DNA repair complex. A 31-amino-acid region of Mdm2 was necessary for binding to Nbs1. Mutation of conserved amino acids in the Nbs1 binding domain of Mdm2 inhibited Mdm2-Nbs1 association and prevented Mdm2 from delaying phosphorylation of H2AX and ATM-S/TQ sites, repair of DNA breaks, and resolution of DNA damage foci. Similarly, the mutation of eight amino acids in the Mdm2 binding domain of Nbs1 inhibited Mdm2-Nbs1 interaction and blocked the ability of Mdm2 to delay DNA break repair. Both Nbs1 and ATM, but not the ubiquitin ligase activity of Mdm2, were necessary to inhibit DNA break repair. Only Mdm2 with an intact Nbs1 binding domain was able to increase the frequency of chromosome/chromatid breaks and the transformation efficiency of cells lacking p53. Therefore, the interaction of Mdm2 with Nbs1 inhibited DNA break repair, leading to chromosome instability and subsequent transformation that was independent of p53.